2015
DOI: 10.1021/acs.iecr.5b01645
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and Mixing Characteristics of Gas–Solid Flow in a Pulsed Spouted Bed

Abstract: The flow behavior and particle motion in a pulsed gas-solid spouted bed was investigated using the Eulerian-Lagrangian approach. The Computational Fluid Dynamics-Discrete Element Method (CFD-DEM) was used to evaluate the gas flow field and particle trajectories. The model was four-way coupled to account for fluid-particle, particle-fluid and particle-particle interactions. A column of 150 mm × 15 mm cross-section and height 750 mm containing 24,500 particles of diameter 2.5 mm was investigated. Gas entered thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Cellulose is a linear polymer of glucose while the hemicellulose fraction of lignocellulosic biomassis generally comprised of different main monosaccharides containing mannose, xylose, galactose, glucose, arabinose, and other residues like galacturonic, 4-o-methyl glucuronic acid. [4][5][6][7][8] Lignin is of the polyaromatic structure possessing linked aromatic units similar to petroleum and it also acts as a resin which fills up the spaces between cellulose and hemicellulose. Unsaturated oxygenates components in lignin-derived bio-oils formed in pyrolysis process cause several undesirable properties including non-volatility, high viscosity, corrosiveness, poor heating value, immiscibility with fossil fuels, thermal instability, and tendency to be polymerized during storage and transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose is a linear polymer of glucose while the hemicellulose fraction of lignocellulosic biomassis generally comprised of different main monosaccharides containing mannose, xylose, galactose, glucose, arabinose, and other residues like galacturonic, 4-o-methyl glucuronic acid. [4][5][6][7][8] Lignin is of the polyaromatic structure possessing linked aromatic units similar to petroleum and it also acts as a resin which fills up the spaces between cellulose and hemicellulose. Unsaturated oxygenates components in lignin-derived bio-oils formed in pyrolysis process cause several undesirable properties including non-volatility, high viscosity, corrosiveness, poor heating value, immiscibility with fossil fuels, thermal instability, and tendency to be polymerized during storage and transportation.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of coal processing technology, coal with a smaller particle size is produced, and more efficient methods are needed to effectively separate coal of less than 6 mm. The general practice is to introduce external forces into the traditional gas-solid fluidized bed, such as in vibrated fluidized bed [23][24][25], magnetically stabilized fluidized bed [26], and pulsating fluidized bed [27,28]. Although these methods play improve the separation effect, they involve increased energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 21 investigated and demonstrated the role of bubbles on solid mixing, and mixing mechanisms were explored in a bubbling fluidized. Luo et al 22,23 and Saidi et al 24 investigated the effect of a draft tube and pulsed gas delivery on the solid mixing characteristics of spouted bed, respectively. However, most prior numerical simulations assumed that particles were spherical.…”
Section: Introductionmentioning
confidence: 99%